Critical language awareness for the heritage context: Development and validation of a measurement questionnaire. (October 2019) - Beaudrie, Sara; Amezcua, Angelica; Loza, Sergio
Critical language awareness (CLA) is increasingly identified as a central component of the Spanish heritage language (SHL) classroom (Leeman, 2005; Martínez, 2003; among others). As a minority language, SHL is subject to sociopolitical, cultural, and economic forces that devalue its status. It is devalued in the eyes of the public, as a legitimate U.S. language, and as something worthy of being maintained. It is essential that students receive instruction not only in the heritage language, but also on the contextual factors that affect the Spanish-English sociopolitical relationship in the United States. Such instruction will enable learners to begin resisting heritage language loss by questioning language ideologies that promote English monolingualism and standard, monolingual Spanish as the ideal norm. The aim of this study was to develop a questionnaire with adequate psychometric properties to measure CLA in the SHL context. The respondents were 301 students enrolled in SHL courses in four U.S. universities. The questionnaire results were submitted to a series of statistical analysis to investigate how well the instrument meets the criteria of reliability and validity specified in this study. The final 19-item instrument had adequate psychometric properties and detected change in the CLA of students in a class where CLA was taught.